2013
DOI: 10.20453/rnp.v66i4.1556
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome alcohólico fetal

Abstract: res

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…• Síndrome Alcohólico Fetal (SAF), fue el primer término de la clasificación en ser descrito, y es el más grave. • Síndrome Alcohólico Fetal Parcial (SAFP), presentan alteraciones en el sistema nervioso central y pueden tener pocas o ninguna anomalía morfológica de carácter externo (Antorán, 2019).…”
Section: Clasificación De Los Trastornos Asociados Al Consumo Materno...unclassified
“…• Síndrome Alcohólico Fetal (SAF), fue el primer término de la clasificación en ser descrito, y es el más grave. • Síndrome Alcohólico Fetal Parcial (SAFP), presentan alteraciones en el sistema nervioso central y pueden tener pocas o ninguna anomalía morfológica de carácter externo (Antorán, 2019).…”
Section: Clasificación De Los Trastornos Asociados Al Consumo Materno...unclassified
“…With the documentation of new cases of FAS, it was observed that the signs initially described were not always present all together and, when they were present, severity levels varied, thus the term Fetal Alcohol Spectrum Disorder (FASD) was proposed (5) . Manifestations of this condition include neurological abnormalities characterized by behavioral disorders, neuropsychomotor development delay, intellectual impairment, and sensory and perceptual changes (6)(7)(8)(9) . There are other labels under the umbrella term FASD owing to the heterogeneity of manifestations: Partial Fetal Alcohol Syndrome (pFAS), Alcohol-Related Birth Defects (ARBD), and Alcohol-Related Neurodevelopmental Disorder (ARND) (1) .…”
Section: Introductionmentioning
confidence: 99%
“…Com a documentação de novos casos sobre a SFA, foi observado que os sinais descritos, inicialmente, nem sempre se apresentavam todos em conjunto e, quando presentes, os graus de severidade eram variados, sendo então proposto o termo Transtorno do Espectro Alcoólico Fetal (TEAF) (5) . Entre as manifestações dessa condição, estão as anormalidades neurológicas, caracterizadas por disfunções comportamentais, atraso no desenvolvimento neuropsicomotor, deficiência intelectual, alterações sensoriais e perceptivas (6)(7)(8)(9) . Ainda, existem outras denominações em função da heterogeneidade das manifestações, como a síndrome fetal do álcool parcial (SFAp), distúrbios ao nascimento relacionados ao álcool (DNRA) e distúrbio do neurodesenvolvimento relacionado ao álcool (DNDRA) (1) .…”
Section: Introductionunclassified